Phylogenetic analysis based on ITS sequences and conditions affecting the type of conidial germination of Bipolaris oryzae - Dela Paz, M. A. G.; Goodwin, P.H.; Raymundo, A.K.; Ardales, E.Y.; Cruz, C. M. Vera (Wiley, 2006)
One taxonomic characteristic of Bipolaris species is the bipolar germination of conidia, but conidia of Bipolaris oryzae, the causal pathogen of brown spot in rice, are regularly observed to show intercalary germination, a characteristic of Drechslera species. The effect of selection, culture media and culture age on type of conidial germination was determined for three brown spot isolates from Cavinti, San Pablo and Palawan in the Philippines, obtained from infected leaves showing typical disease symptoms. Based on the analyses of their ITS1, ITS2 and 5·8S rDNA nucleotide sequences, the local isolates were clearly identified as B. oryzae. Selection for colonies of the three isolates derived from single conidia with either bipolar or intercalary germination had no effect on the number of spores showing bipolar germination in subsequent cultures. Germination on seven different culture media was tested; of these, rabbit food agar and water agar increased the percentage of bipolar germination of conidia, although this varied between isolates. Incubation of the cultures of all three isolates for longer periods prior to harvesting conidia increased the percentage of bipolar‐germinating conidia from c. 40 to c. 90% with 5‐day‐old and 30‐day‐old cultures, respectively.